Evidence of transcription from the late region of the integrated simian virus 40 genome in transformed cells: location of the 5' ends of late transcripts in cells abortively infected and in cells transformed by simian virus 40. - Ernoult-Lange, M (1983)
By means of S1 mapping, we observed that spliced 16S and 19S viral late mRNAs--in addition to early mRNAs--were present in cytoplasmic polyadenylated RNA preparations from simian virus 40-transformed cell lines of rat or mouse origin containing no detectable amount of free viral DNA. The amounts of early and late virus-specific mRNAs in these lines were quantified by hybridization of radioactive cytoplasmic polyadenylated RNA with cloned region-specific restriction fragments. The relative amount of late viral mRNA produced in these transformed cells was found to be of the same order as that produced in simian virus 40-infected, nonpermissive baby mouse kidney cells. Moreover, by using the S1 nuclease protection method, we compared the 5' ends of late mRNAs produced (i) in transformed cells, (ii) in abortively infected mouse cells, and (iii) in the late phase of the lytic cycle. The 5' ends of late mRNAs both in abortively infected and in transformed cells were less heterogeneous than the 5' ends of late mRNAs produced during the lytic cycle; however, they were a subset of the 5' ends of late transcripts produced in the lytic cycle.